اثر نموذج تعليمي بالتشبيهات في تحصيل طالبات الصف الاول الثانوي العلمي في الوراثة الجزيئية - الخوالدة، سالم عبدالعزيز عواد (جامعة اليرموك - عمادة البحث العلمي, 2008)
هدفت هذه الدراسة إلى استقصاء أثر نموذج تعليمي بالتشبيهات، هو النموذج الإيضاحي القائم على الرسوم التخطيطية الثابتة- ثنائية الأبعاد في تحصيل طالبات الصف الأول الثانوي العلمي في مادة الوراثة الجزيئية، مقارنة بالطريقة التقليدية في تدريس الأحياء. تكونت عينة الدراسة من (54) طالبة في شعبتين للصف الأول الثانوي العلمي في إحدى المدارس الثانوية للإناث في مدينة المفرق، ووزعت هاتان الشعبتان عشوائيا لتشكيل المجموعة التجريبية والمجموعة الضابطة. تم تدريس المجموعة التجريبية (ن= 26) باستخدام النموذج الإيضاحي، في حين درست المجموعة الضابطة (ن= 28) بالطريقة التقليدية. لاختبار فرضيات الدراسة تم استخدام تحليل التباين الثنائي المشترك ذي التصميم العاملي Two- way ANCOVA(22) أشارت نتائج الدراسة إلى وجود فروق دالة إحصائيا في تحصيل طالبات الصف الأول الثانوي العلمي في الوراثة الجزيئية تعزى لطريقة التدريس بالنموذج الإيضاحي، لصالح الطالبات اللواتي درسن باستخدام النموذج الإيضاحي. كما بينت النتائج وجود فروق دالة إحصائيا في تحصيل طالبات الصف الأول الثانوي العلمي في الوراثة الجزيئية تعزى للتفكير الشكلي المحسوس، لصالح الطالبات ذوات التفكير المجرد. وبينت النتائج كذلك عدم وجود أثر ذي دلالة إحصائية في تحصيل طالبات الصف الأول الثانوي العلمي في الوراثة الجزيئية يعزى للتفاعل بين طريقة التدريس والتفكير الشكلي. وخلصت الدراسة إلى عدد من التوصيات في ضوء النتائج. This study aimed at investigating the effect of the analogical model based on static two-dimensional illustrations (illustrations model) on female first secondary scientific stream students' achievement in molecular genetics, compared with the traditional method. The sample of the study consisted of 54 female first secondary scientific stream students' in two classes of the same high school located in Mafraq city. The experimental group which consisted of 26 students received instruction using the integrated illustration model. Whereas the control group consisted of 28 students used the traditional method. A pretest-post-test control group design utilising the analysis of covariance (two-way ANCOVA) was used to test the hypotheses of the study. The statistical treatment of the data of the study showed the following findings: - There were statistically significant differences in female first secondary scientific stream students' achievement in molecular genetics that can be attributed to instructional method using the illustration model. Those differences were in favor of the students in the experimental group. - There were statistically significant differences in female first secondary scientific stream students' achievement in molecular genetics that can be attributed to formal thinking using the concrete method. Those differences were in favor of formal thinkers. - There is no significant effect in the female first secondary scientific stream students' achievement in molecular genetics that can be attributed to the interaction between the instructional method and formal thinking. Several recommendations were suggested upon the results of the Study.
622620
Keywords: تدريس الاحياء -- الوراثة الجزيئية -- البرامج التعليمية -- التحصيل الدراسي -- التعليم الثانوي -- طالبات المدارس الثانوية -- طرق التدريس -- الاردن -- الوسائل التعليمية -- الفيزياء